2013
DOI: 10.3390/molecules181113735
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical, Antimicrobial and Antioxidant Properties of Chitosan Films Incorporated with Carvacrol

Abstract: Chitosan films (CF) with carvacrol (CAR) [0.5%, 1.0% and 1.5% v/v] were prepared by the emulsion method. The retained CAR, water solubility, water vapor permeability (WVP), optical, mechanical properties, antibacterial and antioxidant capacity of films were analyzed. The results indicate that the retention of CAR in the CF was ≈50%. The incorporation of CAR to CF decreased the water solubility, the WVP, the yellowing and transparency and the tensile strength, but increased the stiffness. Microcapsules with dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
60
3
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(80 citation statements)
references
References 48 publications
(64 reference statements)
14
60
3
3
Order By: Relevance
“…This highlights the positive effect of films combined with essential oils on film strength. Indeed, several studies report that the oil addition on films reduces the matrix strength when they are combined (Pereda et al, 2012, Binsi et al, 2013, López-Mata et al, 2013. However, in concordance with our findings, it has been reported that the addition of olive oil improves the tensile properties of chitosan films (Pereda et al, 2012).…”
Section: Physical Properties Of the Filmssupporting
confidence: 92%
See 1 more Smart Citation
“…This highlights the positive effect of films combined with essential oils on film strength. Indeed, several studies report that the oil addition on films reduces the matrix strength when they are combined (Pereda et al, 2012, Binsi et al, 2013, López-Mata et al, 2013. However, in concordance with our findings, it has been reported that the addition of olive oil improves the tensile properties of chitosan films (Pereda et al, 2012).…”
Section: Physical Properties Of the Filmssupporting
confidence: 92%
“…The tensile strength evaluated in treatments ranged from 26.53 to 60.94 MPa, the fewer strength films being those where essential oils of cinnamon and thyme (in both tested concentrations) were incorporated in combination, and also the films that containing only chitosan (Ch). The values for control treatment (Ch) was found within the range reported by others (Casariego et al, 2009, Wang et al, 2011, López Mata et al, 2013 for chitosan films, this behavior is linked to several factors such as the chitosan concentration, the degree of acetylation of the molecule, and several others. Contrary to what occurred in combined essential oils, when they were incorporated individually at both 1 % and 2 %, the films were firmest, as it was with TL1 treatment.…”
Section: Physical Properties Of the Filmssupporting
confidence: 82%
“…This is a phenolic compound frequently found in oregano and thyme oil that is also a food additive known to be safe for decades. Carvacrol (Figure 1(a)) has been proven to possess antioxidant and antimicrobial properties against a wide range of microorganisms [15,16]. Other compounds detected in the oregano oil included p-cymene (8.5%) andterpinene (6.4%).…”
Section: Gas Chromatography Analysis Of Essential Oilsmentioning
confidence: 99%
“…Indeed, carvacrol, the main component in oregano, thyme, marjoram, and summer savory oil, has been extensively studied and applied as a flavouring and antimicrobial agent in numerous foodstuffs, such as sweets, chewing gum, and beverages [14]. Besides its antimicrobial activity, barrier and antioxidant properties can be enhanced by incorporating these substances into a polymer matrix [15,16]. Furthermore, study has been conducted into combinations of chitosan film with various essential oils, for example, rosemary [17], lemon [3], thyme [18], oregano [8], basil [19], cinnamon, and clove [7] with regard to their effect on antimicrobial, mechanical, and barrier properties.…”
Section: Introductionmentioning
confidence: 99%
“…The variability in those values and the increase in the last days of our study might be due to rigor mortis in muscle, during which WRC is very low but later increases (Huss, 1988). Another possible factor responsible for the variability may be the polarity of the polymer, as usually greater polarity is associated with lower porosity and water loss (Jeon et al, 2002;Mohan et al, 2012); the incorporation of carvacrol also produces a more compact network (López-Mata et al, 2013).…”
Section: Water Retention Capacitymentioning
confidence: 99%